2010
DOI: 10.1111/j.1463-1318.2010.01999.x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic colorectal surgery: hype or new hope? A systematic review of robotics in colorectal surgery

Abstract: Aim:Robotic colorectal surgery is an emerging field and may offer a solution to some of the difficulties inherent to conventional laparoscopic surgery. The aim of this review is to provide a comprehensive and critical analysis of the available literature on the use of robotic technology in colorectal surgery. Methods:Studies reporting outcomes of robotic colorectal surgery were identified by systematic searches of electronic databases. Outcomes examined included operating time, length of stay, blood loss, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 34 publications
2
31
1
2
Order By: Relevance
“…The laparoscopic technique offers particular advantages for older patients due to reductions in length of hospital stay [14], morbidity and mortality rates, and direct cost of care [15,17]. Robotic surgery can achieve the same results as those reported herein and as demonstrated in a review in 2009 [34]. These authors reported the results of 288 colorectal robotic procedures.…”
Section: Discussionsupporting
confidence: 84%
“…The laparoscopic technique offers particular advantages for older patients due to reductions in length of hospital stay [14], morbidity and mortality rates, and direct cost of care [15,17]. Robotic surgery can achieve the same results as those reported herein and as demonstrated in a review in 2009 [34]. These authors reported the results of 288 colorectal robotic procedures.…”
Section: Discussionsupporting
confidence: 84%
“…19,20 In literature, there are conflicting reports about the operative time when comparing robotic surgery to laparoscopic surgery in rectal cancer patients. 14,17,21 In our series, the operative time was longer compared to that of our laparoscopic TME series. 7 Probably, the operative time would be shorter with increased experience.…”
Section: Discussioncontrasting
confidence: 60%
“…This includes disposable drapes, specialized device lubricant for the robotic instruments, and the need to replace the instrument working arms every 10-20 procedures [15][16][17]. Together with the Gel POINT Path Access Platform, the per-case cost of a single robotic TAMIS case is approximately $1,500 USD.…”
Section: Discussionmentioning
confidence: 99%